Ground bias: A driver for skepticisms about space exploration - Milligan, Tony (Frontiers in Astronomy and Space Sciences, 2022)
This paper introduces and develops the concept of “ground bias.” The bias in question involves a background underestimation of the importance of space for an understanding of terrestrial processes. Underestimation then operates as a driver for various kinds of skepticism about space exploration. such as those involved in climate change. Ground bias is also more widespread than skepticism about space exploration and does not, on its own, entail it. There may need to be some further factor (such as populist political critique, fears about technology, or a generalized pessimism about the future of humanity) before space skepticism is embraced. Nonetheless, an appeal to ground bias can help to explain the stubborn persistence of skepticism about space exploration in the face of successive failed predictions about the negative impact of space programs upon humanity. The arc of the paper moves from an overview of space skepticisms to a clarification of the ground bias concept. The formal argument of the paper (that this bias helps to explain the persistence of skepticism about space) is largely a foil to help set up the ground bias concept. The final section considers the standing of ground bias by comparison with other sorts of human bias, up to and including forms of irrational prejudice. Ground bias is significantly different from these, and closer to human biases about time (e.g., thinking of the future as more important than the past, and near events as more important than distant ones). However, it is also a good deal newer than bias about time, and less rooted in our human makeup.